Microstructured Hydrogels to Guide Self‐Assembly and Function of Lung Alveolospheres. Issue 28 (7th June 2022) - Loebel, Claudia; Weiner, Aaron I.; Eiken, Madeline K.; Katzen, Jeremy B.; Morley, Michael P.; Bala, Vikram; Cardenas‐Diaz, Fabian L.; Davidson, Matthew D.; Shiraishi, Kazushige; Basil, Maria C.; Ferguson, Laura T.; Spence, Jason R.; et al.
Abstract: Epithelial cell organoids have increased opportunities to probe questions on tissue development and disease in vitro and for therapeutic cell transplantation. Despite their potential, current protocols to grow these organoids almost exclusively depend on culture within 3D Matrigel, which limits defined culture conditions, introduces animal components, and results in heterogenous organoids (i.e., shape, size, composition). Here, a method is described that relies on hyaluronic acid hydrogels for the generation and expansion of lung alveolar organoids (alveolospheres). Using synthetic hydrogels with defined chemical and physical properties, human‐induced pluripotent stem cell (iPSC)‐derived alveolar type 2 cells (iAT2s) self‐assemble into alveolospheres and propagate in Matrigel‐free conditions. By engineering predefined microcavities within these hydrogels, the heterogeneity of alveolosphere size and structure is reduced when compared to 3D culture, while maintaining the alveolar type 2 cell fate of human iAT2‐derived progenitor cells. This hydrogel system is a facile and accessible system for the culture of iPSC‐derived lung progenitors and the method can be expanded to the culture of primary mouse tissue derived AT2 and other epithelial progenitor and stem cell aggregates. Abstract : Epithelial cell organoids provide a system to probe tissue development and disease in vitro and for cell transplantation. Within the lung field, alveolar organoids almost exclusively depend on Matrigel, which limits defined culture conditions. In this work, the design of an accessible hydrogel system with predefined microcavities to generate alveolar organoids through self‐assembly and maintenance of progenitor cell fate and function is described.